PWE-033 Comprehensive assessment of outcomes including costs and survival in younger vs older patients undergoing surgical management of oesophageal cancer. (28th May 2012) - Markar, S R; Karthikesalingam, A; Low, D
Abstract : Introduction: The aim of this study was to compare disease presentation, clinical and pathological staging, peri-operative outcome, costs and long-term survival of patients 50 years and under (≤50), and those over 50 (>50) undergoing oesophagectomy for oesophageal malignancy. Methods: All patients undergoing oesophagectomy by a single surgeon for cancer between 1991 and 2011 had information prospectively entered in an IRB-approved database. These two groups were compared for symptomatic presentation that is, length of dysphagia and degree of weight loss, clinical and pathologic stage, neoadjuvant therapy, medical co-morbidities, operative outcomes including complications, treatment costs and survival. Results: In total 493 patients underwent surgical resection for oesophageal malignancy from 1991 to 2011. 58 of these patients were ≤50 yrs (44±4.7), and 435 patients were > 50 years (67±8.44). Younger patients demonstrated an increased likelihood for delayed presentation as shown by an increased length of dysphagia (5.79±13.19 vs 3.4±6.97 months) and increased weight loss (14.69±21.12 vs 10.13±14.55 lbs). Older patients typically presented with more cardiac comorbidities. Clinical stage was similar, the younger cohort of patients demonstrated a significantly increased incidence of adenocarcinoma (93.1% vs 82.53%) and Signet ring pathology (10.34% vs 6.44%). Treatment approach was similar except younger patients were more likely to receive neoadjuvant chemoradiotherapy for stage IIA disease (53.85% vs 27.1%) and chemotherapy alone for stage IIB (42.86% vs 11.11%). Length of operation, blood loss, transfusion requirements and length of hospital stay were similar for both groups. However, patients ≤50 years demonstrated significantly shorter Intensive care unit stay (1.43±1.08 vs 2.08±2.59 days), reduced incidence of post-operative complications (29.31% vs 48.51%) and in subset analysis reduced overall cost ($20 133±7048 vs $23 921±10 787). No significant difference was noted in final pathological stage, incidence of complete response to therapy or positive resection margins. Average follow-up was approximately 4 years in the ≤50 age group and 3.5 years in the >50 age group with no difference noted in 5-year survival (46.15% vs 38.33% (p=0.35). Log-rank testing also showed no difference between under 50 and over 50 age groups for all cause mortality during the study period (χ 2 0.432; p=0.511). Conclusion: This study demonstrates younger patients have fewer complications and less overall treatment costs following oesophagectomy. In spite of having a more delayed presentation, and a higher incidence of adenocarcinoma younger patients presented with a similar stage and demonstrated similar overall survival. Competing interests: S Markar Grant/Research Support from: Ryan Hill Research Foundation, A Karthikesalingam: None declared, D Low: None declared.